Evolution of Human Factors Research and Studies of Health Information Technologies: The Role of Patient Safety - Beuscart-Zéphir, M.C.; Borycki, E.; Carayon, P.; Jaspers, M.W.M.; Pelayo, S. (Yearbook of Medical Informatics, 2013)
Objectives: The objective of this survey paper is to present and explain the impact of recent regulations and patient safety initiatives (EU, US and Canada) on Human Factors (HF) /Usability studies and research focusing on Health Information Technology (HIT).Methods: The authors have selected the most prominent of these recent regulations and initiatives, which rely on validated HF and usability methods and concepts and aim at enhancing the specific process of identification and prevention of technology-induced errors throughout the lifecycle of HIT.Results: The analysis highlights several points of consensus: 1) safety initiatives or regulations applicable to Medical Devices (MD) tend to extend to HIT, 2) Usability is considered a fundamental dimension of HIT safety, 3) HF/Usability methods and the overall Human Centred Design (HCD) approach are considered efficient solutions to ensure the design of safe and usable HIT. However, it appears that MD manufacturers, and a fortiori HIT designers and developers are still far from being able to routinely apply HCD to their productsDiscussion and conclusion: On the research side, we need to analyze manufacturers' difficulties with the application of the HCD process and imposed standards. For each given category of HIT, we need to identify the fundamental usability dimensions and design principles likely to impact patient safety independently of workplace settings or organizations. These should be described in terms of usability flaws, corresponding usage problems experienced by users and related outcomes. This approach requires good quality and well structured reporting of Human Factors / Usability research studies on HIT.
Keywords: Human engineering; usability; patient safety; regulation; medical informatics applications